The Role of Government in Eradicating Illegal Sand Mining in Julukanaya Village, Pallangga District, Gowa Regency - Halim, Abdul; Mekka, Suparman; Aisyah, St.Nur (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to determine the role of the government in eradicating illegal sand mining in Julukanaya village, Pallangga sub-district, Gowa district. The method used in the study is a descriptive qualitative approach that explores the role and strategy of the government in eradicating illegal sand mining comprehensively and in depth. The data collection technique used in this study was by conducting on-site observations, interviews and documentation. Based on the results of the study, it shows that the role of the government in eradicating illegal sand mining in Julukanaya village, Pallangga sub-district, Gowa district is still weak due to the lack of communication between the village government and the sub-district government and the lack of providing a deterrent effect to mining perpetrators. The government with various efforts that have been made has not been effective in stopping illegal sand mining. The actions that must be taken by the village government together with the police are that the village government needs to increase the effectiveness of law enforcement against illegal mining perpetrators.